TECHNOLOGICAL BARRIERS TO THE DEVELOPMENT OF THE GRAIN INDUSTRY IN RUSSIA - O. A. Yeremchenko (Ekonomika Nauki)
In recent years, there has been a significant deterioration in the quality of Russian grain and a reduction in the production of food wheat. In the structure of the crop in 2016, food wheat was 28%, the remaining 78% was the fourth and fifth grade wheat, used for the production of forage grains. Five years ago, the ratio of food wheat and wheat of the fourth and fifth grades was 1: 1. The article considers four main groups of technological barriers affecting the development of the domestic grain industry. The patent – conjunctural analysis of each direction was carried out, the key laws of its development, and the availability of a raw and infrastructural base for its development, scientific and technical rewards for the further development of the industry were allocated. The conclusion about the need for an integrated approach to the development of all areas in general was done. It is shown that the development of related technologies in the grain industry, such as precision farming, can not significantly improve the efficiency of the industry in the absence of strong basic technologies such as grain selection and seed conservation, fertilizer production and soil quality improvement, production of chemical plant protection products, storage of grain.